Telehealth delivery of adherence and medication management system improves outcomes in inner‐city children with asthma. Issue 4 (6th January 2020) - Lin, Nancy Y.; Ramsey, Rachelle R.; Miller, James L.; McDowell, Karen M.; Zhang, Nanhua; Hommel, Kevin; Guilbert, Theresa W.
Abstract: Healthcare disparities exist in pediatric asthma in the United States. Children from minority, low‐income families in inner‐city areas encounter barriers to healthcare, leading to greater rates of poorly controlled asthma and healthcare utilization. Finding an effective way to deliver high‐quality healthcare to this underserved population to improve outcomes, reduce morbidity and mortality, and reduce healthcare utilization is of the utmost importance. The purpose of this study was to assess the feasibility and efficacy of a novel school‐based care delivery model that incorporates video‐based telehealth (VBT) medical and self‐management visits with electronic inhaler monitoring to improve asthma outcomes. Over a 6‐month period, children from inner‐city, low‐income schools with uncontrolled asthma completed seven scheduled medical visits with an asthma specialist and five self‐management visits with an adherence psychologist at school using VBT. Composite Asthma Severity Index (CASI) scores and electronic inhaler monitor data were recorded and analyzed. A total of 21 patients were enrolled in the study. Study subjects with higher baseline severity (CASI ≥ 4 at visit 1) demonstrated a greater reduction in their score than those with lower baseline severity (CASI < 4 at visit 1). The CASI domains showed improvement in daytime symptoms, nighttime symptoms, and exacerbations. Adherence results demonstrated a significant improvement in adherence from baseline to postintervention. Study retention was 100%. This study demonstrates that a multicomponent medical and behavioral interventional program delivered by VBT to a school‐based setting is feasible and can significantly improve asthma outcomes and care in a challenging population.